Copy number variants and their association with intracerebral hemorrhage risk: a case-control study - Prapiadou, Savvina; Langefeld, Carl D.; Sekar, Padmini; Comeau, Mary; Howard, Timothy; Kimball, Tamara N.; Bowang, Chen; Hyacinth, Hyacinth I.; Rosand, Jonathan; Anderson, Christopher D.; Grond-Ginsbach, Caspar; Woo, Daniel; et al. (Annals of Clinical and Translational Neurology, 2025)
Introduction Intracerebral Hemorrhage (ICH) is a leading cause of morbidity and mortality worldwide and lacks effective therapeutic interventions. Despite previous studies, the genetic underpinnings of ICH remain poorly understood. We sought to investigate the role of copy number variants (CNVs) in ICH pathophysiology to identify novel etiological mechanisms and therapeutic targets. Methods We analyzed microarray data from ICH cases and controls using PennCNV software, followed by rigorous quality control and CNV validation. This case-control study explored associations between large, rare CNVs and ICH risk, examining CNVs that are genic, contain ohnologs, or span multiple genes. Functional enrichment analysis was also conducted to identify overrepresented CNVs in biological processes relevant to ICH. Results The study included 649 cases and 437 controls who passed quality control. Cases were more likely to have genic CNVs compared to controls (39.6% vs. 32.5%, p value = 0.02) after adjusting for age, sex, hypertension, and admixture. In pathway analysis, CNVs associated with cholesterol biosynthesis (6.3% vs. 3.2%, p value = 0.04) and blood vessel development were more common in cases (8.2% vs. 5.3%, p value = 0.06). While associations were observed at nominal significance (p < 0.05), none withstood correction for multiple comparisons. Discussion Our study represents the first CNV analysis of ICH risk. While significant associations between large, rare CNVs and ICH risk were not established, the findings indicate potential pathways for further research. The identified trends warrant further investigation, and our methodological framework provides a foundation for future large-scale studies aimed at elucidating the role of CNVs in ICH pathogenesis and outcomes.
Gesehen am 10.12.2025